2013
DOI: 10.1155/2013/713060
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects ofHyptis albidaChloroform Extract on Lipopolysaccharide-Stimulated Peritoneal Macrophages

Abstract: We examined the effects of a chloroform extract of Hyptis albida (CHA) on inflammatory responses in mouse lipopolysaccharide (LPS) induced peritoneal macrophages. Our findings indicate that CHA inhibits LPS-induced production of tumor necrosis factor (TNF-α) and interleukin-6 (IL-6). During the process, levels of cyclooxygenase-2 (COX-2), nitric oxide synthase (iNOS), and nitric oxide (NO) increased in the mouse peritoneal macrophages; however, the extract suppressed them significantly. These results provide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…During inflammation, matrix metalloproteinases (MMPs) are also induced and are important for regulating immune cell development, effector function, migration and ligand–receptor interactions, as well as activating signal transduction pathways [ 78 ]. Due to these modulations, the LPS-induced model is excellent for the screening and subsequent evaluation of potential drugs or natural products on the inflammatory pathway [ 79 ]. LPS induction causes endotoxemia, which is related to a significant increase in cardiac dysfunction [ 80 ], triggered via toll-like receptor 4 (TLR-4)-mediated inflammatory responses.…”
Section: Anti-inflammatory Actions Of Squalenementioning
confidence: 99%
“…During inflammation, matrix metalloproteinases (MMPs) are also induced and are important for regulating immune cell development, effector function, migration and ligand–receptor interactions, as well as activating signal transduction pathways [ 78 ]. Due to these modulations, the LPS-induced model is excellent for the screening and subsequent evaluation of potential drugs or natural products on the inflammatory pathway [ 79 ]. LPS induction causes endotoxemia, which is related to a significant increase in cardiac dysfunction [ 80 ], triggered via toll-like receptor 4 (TLR-4)-mediated inflammatory responses.…”
Section: Anti-inflammatory Actions Of Squalenementioning
confidence: 99%
“…Importantly, matrix metalloproteinases (MMPs) regulate aspects of immune cell development, effector function, migration and ligand-receptor interactions and activate signal transduction pathways that control cytokine biosynthesis and direct systemic inflammation or barrier immunity. For this reason, the stimulation with LPS constitutes an excellent model for the screening and subsequent evaluation of the effects of candidate drugs on the inflammatory pathway (Sanchez Miranda, Perez Ramos, Fresan Orozco, Zavala Sanchez, & Perez Gutierrez, 2013). Therefore, we investigated the anti-inflammatory activity of squalene on LPS-stimulated murine peritoneal macrophages and human blood monocytes and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Hyptis albida ) on inflammatory responses in mouse lipopolysaccharide (LPS) induced peritoneal macrophages were evaluated. The results demonstrated that the extract was able in inhibit LPS-induced production of TNF-α and interleukin-6, signaling molecules in the inflammatory cascade ( Sánchez Miranda et al, 2013 ). Besides, the essential oil of Cantinoa americana (syn.…”
Section: Biological Investigationsmentioning
confidence: 99%